Analysis Factors Affecting the Implementation of Pregnancy Exercise Program: Cross-Sectional Study at Margorejo Health Center, Metro City, Lampung - Putri Azzadelia Childrika; Septi Widiyanti; Ika Oktaviani; Sri Lestariningsih (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
Physical activity during pregnancy, such as pregnancy exercise, has significant benefits for maternal and fetal health. However, participation among pregnant women in exercise programs remains low. This study aims to identify factors influencing this participation in Metro City, Lampung Province. This research employs a quantitative design with a cross-sectional approach. A total of 70 respondents were selected through accidental sampling. Data were collected using a validated and reliable questionnaire. Data analysis was conducted using logistic regression to identify the relationship between independent variables and participation in pregnancy exercise. The findings indicate that knowledge, attitude, family support, accessibility of infrastructure, and interaction with health workers significantly influence pregnant women's participation in pregnancy exercise. Conversely, age, education, occupation, parity, and distance travelled did not show significant effects. This study emphasizes the importance of enhancing knowledge and social support to encourage pregnant women's participation in physical activities. The implications of these findings suggest the need for intervention programs involving health workers and improved infrastructure to support maternal and child health.